2015
DOI: 10.3164/jcbn.15-3
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end-products: modifiable environmental factors profoundly mediate insulin resistance

Abstract: Advanced glycation end-products are toxic by-products of metabolism and are also acquired from high-temperature processed foods. They promote oxidative damage to proteins, lipids and nucleotides. Aging and chronic diseases are strongly associated with markers for oxidative stress, especially advanced glycation end-products, and resistance to peripheral insulin-mediated glucose uptake. Modifiable environmental factors including high levels of refined and simple carbohydrate diets, hypercaloric diets and sedenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 179 publications
(284 reference statements)
1
52
0
1
Order By: Relevance
“…Yet the possibility of unmeasured residual confounding cannot be ruled out as data on heme iron were mostly based on observational studies. For example, nitrites and other preservatives in processed meat, as well as advanced glycation end products formed during the high-temperature cooking of animal-derived foods, have been shown to contribute to insulin resistance (72)(73)(74). Findings on dietary nonheme iron intakes and iron supplement are inconclusive in general.…”
Section: Discussionmentioning
confidence: 92%
“…Yet the possibility of unmeasured residual confounding cannot be ruled out as data on heme iron were mostly based on observational studies. For example, nitrites and other preservatives in processed meat, as well as advanced glycation end products formed during the high-temperature cooking of animal-derived foods, have been shown to contribute to insulin resistance (72)(73)(74). Findings on dietary nonheme iron intakes and iron supplement are inconclusive in general.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies show the contribution of advanced glycation end products (AGEs) in the origin and progression of certain chronic diseases, as well as MetS . AGEs are a group of prooxidant and cytotoxic compounds, derived from the nonenzymatic glycation of proteins, lipids, and nuclear acids via a complex sequence of reactions referred as the Maillard reaction .…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, lipids initiate the formation of free radicals by lipid peroxidation, and therefore they are a significant contributor to AGE formation (Rizzi ; Ottum et al . ). However, comparing the CML content of the food items with similar ingredients, we found that although The CML content was related to the type of ingredients, there was not necessarily a connection between one specific ingredient and the CML level, as shown in Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Consequently, a diet rich in protein and carbohydrate causes higher concentrations of AGEs (CML or AGE-fl), and high quantities of AGE-modified proteins were produced with increasing temperature (Uribarri and Tuttle 2006;Frolov et al 2014). Likewise, lipids initiate the formation of free radicals by lipid peroxidation, and therefore they are a significant contributor to AGE formation (Rizzi 2003;Ottum et al 2015). However, comparing the CML content of the food items with similar ingredients, we found that although The CML content was related to the type of ingredients, there was not necessarily a connection between one specific ingredient and the CML level, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%